Effects of meningitis and encephalitis on oxidative state of blood and cerebrospinal fluid - Akarsu, Saadet; Yilmaz, Seval; Ozan, Sema; Benzer, Fulya; Kurt, A. Nese Citak; Kurt, Abdullah (Georg Thieme Verlag Kg, 2008)
Recent studies have shown that the oxidative state plays an important role in the pathophysiology of neuroinflammatory diseases. Determination of erythrocyte arginase, and catalase (CAT), and also plasma and cerebrospinal fluid (CSF) malondialdehyde (MDA), and nitric oxide (NO) concentrations were measured to establish differences between antioxidant state and lipid peroxidationto assess prognosis in neuroinflammatory disease. Three groups were studied, meningitis (n=28), encephalitis (n=30), and a control group (n=40) for the spectrophotometric measurements of arginase, and CAT activities in erythrocytes, thiosemicarbazide diacetylmonoxime, and Aebi methods were used respectively. Plasma and CSF MDA levels were analyzed with a modified Yagi method and NO levels were assessed using spectrophotometric methods using the Griess reaction. Levels of erythrocyte arginase, erythrocyte CAT, and CSF NO differed between meningitis and encephalitis (P < 0.05). While levels of erythrocyte CAT, and CSF MDA, plasma NO and CSF NO concentrations differed between the meningitis group and controls (P < 0.05). Concentrations of erythrocyte arginase, CSFMDA and plasma NO differed between encephalitis and control groups (P < 0.05). All tests in the study except erythrocyte arginase and plasma MDA differed between meningitis cases and controls (P < 0.05). In the meningitis and encephalitis cases, studied oxidative states in blood, and CSF were affected at different levels, meningitis being more severe.
Keywords: Meningitis; encephalitis; cerebrospinal fluid; oxidant; antioxidant